CUSTOMER SATISFACTION ON E-BANKING SERVICES (WITH SPECIAL REFERENCE TO STATE BANK OF INDIA (SBI), ARIYALUR BRANCH) - KOLANCHINATHAN, G.; ELANGO, Dr.S. (The journal of contemporary issues in business and government, 2021)
E-Banking is your personal banking service on the Internet, protected with bank identifiers. It is available anywhere, anytime. E-Banking allows you to pay invoices to Finnish and foreign recipients easily and securely. You can also check your account balances and transactions. You can order a new card, withdraw a loan granted to you and make mutual fund subscriptions. You access e-Banking services by obtaining bank identifiers. E-Banking as such is free of charge but commissions and fees in accordance with the service tariff will be levied on orders and other transactions carried out through e-Banking. E-Banking allows you to pay invoices to Finnish and foreign recipients easily and securely. You can also check your account balances and transactions. You can order a new card, withdraw a loan granted to you and make mutual fund subscriptions. You access e-Banking services by obtaining bank identifiers. E-Banking as such is free of charge but commissions and fees in accordance with the service tariff will be levied on orders and other transactions carried out through e-Banking. The password for online banking is normally not the same as for telephone banking. Financial institutions now routinely allocate customers numbers, whether or not customers have indicated an intention to access their online banking facility.